2013
DOI: 10.1210/en.2012-2245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Specific Uptake and Retention Mechanism for 25-Hydroxyvitamin D (25OHD) in Skeletal Muscle Cells

Abstract: Little is known about the mechanism for the prolonged residence time of 25-hydroxyvitamin D (25OHD) in blood. Several lines of evidence led us to propose that skeletal muscle could function as the site of an extravascular pool of 25OHD. In vitro studies investigated the capacity of differentiated C2 murine muscle cells to take up and release 25OHD, in comparison with other cell types and the involvement of the membrane protein megalin in these mechanisms. When C2 cells are differentiated into myotubes, the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 40 publications
7
101
2
Order By: Relevance
“…Another question is whether vitamin D's effects in bone and muscle are truly integrated or rather independent. In support of the former, osteoblast VDR modulates the effect of muscle loading on bone and vitamin D, sequestered within muscle fibers, may diffuse to adjacent bone under the influence of local stimuli (Abboud et al, 2013). Furthermore, vitamin D regulates paracrine factors considered to facilitate bone-muscle crosstalk -osteocalcin and, possibly, IL6 and myostatin (Morrison et al, 1989;Schleithoff et al, 2006;Szulc et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another question is whether vitamin D's effects in bone and muscle are truly integrated or rather independent. In support of the former, osteoblast VDR modulates the effect of muscle loading on bone and vitamin D, sequestered within muscle fibers, may diffuse to adjacent bone under the influence of local stimuli (Abboud et al, 2013). Furthermore, vitamin D regulates paracrine factors considered to facilitate bone-muscle crosstalk -osteocalcin and, possibly, IL6 and myostatin (Morrison et al, 1989;Schleithoff et al, 2006;Szulc et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Regulated by local and systemic vitamin D signals, bone is the major depot for calcium, an essential mineral in muscle contraction, morphology and plasticity. Conversely, skeletal muscle is emerging as a major storage site for vitamin D from where it may diffuse back into the circulation or possibly, into adjacent bone, following specific signals (Abboud et al, 2013;Girgis et al, 2014d). Thus, vitamin D may have complementary effects in bone and muscle, further supporting the integration of these two tissues.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in animal studies, it was shown that after uptake into mature muscle cells, 25(OH)D is held there by vitamin D binding protein. This sequestration by the skeletal muscle could protect 25(OH)D from hepatic degradation and thus could provide a functional store to maintain vitamin D status (48). However, more data are needed to clarify these complex relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, serum/plasma 25(OH)D does not reflect the storage of vitamin D within the tissues, which can be converted to calcitriol by tissutal 1a-hydroxylase, and the whole vitamin D bioavailability, which also depends on the presence of catabolic metabolites and protein transport in the blood [5]. Recent studies have demonstrated a direct uptake of 25(OH)D by skeletal myocytes, which would internally retain 25(OH)D binded to VDBP [6]. This While the hydroxylation of the side chain of 25(OH)D leads to the production of inactive metabolites, alternative modifications form metabolites, such as the epimer 25(OH)-3-epi-D, capable of binding and activating the VDR [7].…”
Section: Introductionmentioning
confidence: 99%